Juvenile diabetes and systemic sclerosis: just a coincidence? - Greta Mastrangelo; Alessandra Meneghel; Giorgia Martini; Carlo Moretti; Francesco Zulian (BMC, 2022)
Abstract Background Limited joint mobility (LJM), previously known as cheiroarthropathy, refers to the presence of reduced extension at the finger joints in people with diabetes and may be associated with scleroderma-like syndromes such as diabetic sclerodactyly. While scleroderma-like syndromes and LJM have been observed in patients with long-term diabetes and associated complications, the coexistence of diabetes with Juvenile systemic sclerosis (jSSc) is rarely described. Case presentation We describe the case of a 14-year-old boy with long-lasting type 1 diabetes (T1D) and suspected LJM associated with Raynaud phenomenon, sclerodactyly and tapering of the fingertips. A comprehensive work-up showed positive autoantibodies (ANA, anti-Ro-52, anti-Mi-2b), abnormal nailfold capillaroscopy with a scleroderma pattern, interstitial lung disease and cardiac involvement. The overall clinical picture was consistent with the diagnosis of jSSc. Conclusions LJM can be the initial sign of underlying systemic sclerosis. Nailfold capillaroscopy may help differentiate jSSc from classical LJM in pediatric patients with T1D and finger contractures or skin induration of no clear origin. This case report provides a starting point for a novel hypothesis regarding the pathogenesis of jSSc. The association between T1D and jSSc may be more than a coincidence and could suggest a relationship between glucose metabolism, fibrosis and microangiopathy.